Development and in Vitro Evaluation of CRISPR-Cas9-Engineered CAR-NK Cells Targeting Solid Tumors - Abdulraheem Mohamed A; Thaer Hamid A. Hajeej; Shakir Mahdi Saleh (American Journal of Biodiversity, 2026)
The use of chimeric antigen receptor-natural killer (CAR-NK) cells through adoptive transfer has emerged as a possible replacement for CAR-T treatment in solid tumors because of their innate cytotoxicity and a lower probability of cytokine release syndrome. However, limitations such as lack of persistence, inhibitory tumor microenvironment (TME) checkpoints, and heterogeneous antigen expression have made it difficult to achieve the desired effect. Our approach was to create a second-generation CAR structure directed at a model solid-tumor antigen (the mesothelin analogue) and to introduce a membrane-bound IL-15 cassette to support longevity. In addition, we used CRISPR-Cas9 ribonucleoprotein (RNP) electroporation to eliminate three inhibitory loci (TIGIT, CBLB, NKG2A) in NK-92 cells, followed by lentiviral CAR transduction under standardized feeder-free culture conditions. The average in vitro editing efficiency was 78.5% ± 6.8% (mean ± SD) across the three loci, while CAR expression on NK-92 reached 82.1% ± 5.4%. The CRISPR-edited CAR-NK cells exhibited higher cytotoxicity than the non-edited CAR-NK ones at the time point of 24 h (mean lysis was 72.3% ± 9.1% vs 54.8% ± 10.4%, p < 0.01) and let out more IFN-γ and IL-2 in the co-culture supernatants (IFN-γ : 825 ± 312 pg/mL vs 420 ± 210 pg/mL, p < 0.01 ; IL-2: 148 ± 60 pg/mL vs 86 ± 42 pg/mL, p < 0.05). The methodology employed for the statistical comparisons was two-tailed t tests and nonparametric confirmation where normality of the distributions was not observed. The usage of CRISPR-Cas9 to edit the inhibitory checkpoints along with CAR expression and IL-15 led to a significant improvement in the cytotoxicity of NK-92 towards the tumor cells in vitro, which is in accordance with the findings of recent researches that ablation of checkpoints (e.g., TIGIT, CBLB, NKG2A) has made NKs more fit and functionally stronger. The results obtained in this study present a feasibility for rational off-the-shelf, CRISPR-engineered CAR-NK therapies for solid tumors and an experimental in vitro toolkit for further translational development that is easy to handle, while they also bring to light the necessity for safety and off-target assessment in clinical translation as a priority.